(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The bond behavior of steel and GFRP bars in concrete is one of the most important issues in reinforced concrete structures and depends on several factors, such as the structural characteristics, bar and concrete properties. Glass fiber-reinforced polymer (GFRP) reinforcements are taken as an alternative solution for the deterioration of civil infrastructures. GFRP bars have received increasing attention due to low cost compared to steel bars. Bond characteristic of GFRP bars in concrete is the most critical parameter for implementation of the material to the corrosion-free concrete structures. This paper offers an extensive discussion of the bond performance of reinforcement bars (steel and GFRP) with concrete, considering the bond mechanism, parameters affecting bond strength, and bond test methodologies. Finally, a comprehensive review is presented about a previous study that was conducted to investigate the bond behavior of steel and GFRP bars embedded in concrete.